"Ten pound touts": Post-conflict trust and the legacy of counterinsurgency in Northern Ireland - Kristin M. Bakke; Kit Rickard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper explores the legacies of wartime rebel governance and counterinsurgency tactics. Insurgents rely on civilian support for resources, information, and cover. To defeat insurgents, the state attempts to extract information from communities where support for insurgents is highest. We argue that strong norms against civilian collaboration emerge in these areas, which may have long legacies for local community trust. To explore these legacies, we conduct a case study of post-conflict Northern Ireland. While both Republican and Loyalist paramilitary groups established wartime institutions, the counterinsurgency targeted Republican groups in urban areas with the use of informants. Drawing on secondary literature and a survey, we show that strong norms against informers-'touts'-persist long after the end of the conflict in Republican strongholds. These areas show lower levels of local community trust than their Loyalist counterparts. The Northern Irish case demonstrates the detrimental effects of dynamics likely to shape other post-conflict states.
Keywords: 330; trust; counterinsurgency; post-conflict; rebel governance; survey